PEMBERDAYAAN KADER TANGGUH PEDULI LEPRA DALAM PELACAKAN KUSTA: EMPOWERMENT OF TANGGUH CARE FOR LEPRA IN LEPROSY TRACKING - Kurniadi Kurniadi; Aniharyati Aniharyati; Abdul haris (Jurnal Pengabdian Masyarakat Multidisiplin, 2023)
Introduction: Social problems caused by leprosy arise due to the fear that leprosy sufferers experience in society (leprophobia). Low knowledge, lack of socialization in society, and bad stigma in society, resulting in a lack of community participation in eradicating leprosy. After India and Brazil, Indonesia is one of the developing countries with the highest number of newly diagnosed sufferers. leprosy case. third highest in the world. Purpose: The purpose of this community service is to increase public understanding of early detection of leprosy in Kolo Kota Bima Village. Method: The method used in this community service is health education and training on the identification of leprosy by tough cadres caring for leprosy. Community service activities were carried out in the Kolo Community Health Center hall, Bima City, which was attended by 15 cadres, 5 enumerators, the Head of the Kolo Community Health Center, the KTU of the Kolo Health Center, and servants. This activity is training for cadres and counseling about leprosy including the meaning, signs, symptoms, management, process of transmission of leprosy. Results: The results of the pre-test community service were 27% of cadres with good knowledge. While the post test 100% of cadres have good knowledge. The results of this dedication are important to assist the government's efforts to improve national health development. Conclusions and Recommendations: All targeted leprosy care cadres have understood the signs and symptoms of leprosy. It is hoped that community service will be carried out regularly and to health cadres so that leprosy cases can be handled immediately.